Effect of Puerarin on EBI after SAH - ZENG,Xiangwu (2022)
Abstract Objective The neuroinflammatory reaction activated after the activation of microglia plays a critical role in the pathological mechanism of early brain injury after subarachnoid hemorrhage. The inhibitory effect of Puerarin on inflammatory response plays a protective effect against various diseases. The present study mainly explored whether Puerarin alleviates the inflammation after SAH by inhibiting the Notchl pathway. Methods: Rat SAH model was induced by internal carotid artery puncture. The content of brain edema was evaluated and assessed. Evans blue staining was used to detect the degree of blood-brain barrier damage. FJC staining was used to assess neuronal apoptosis. Western blot method was employed to detect the expressions of Notchl receptor and downstream factors to clarify the protective effect and specific mechanism of Puerarin on brain tissue after SAH. Results: Puerarin can attenuate the brain edema and blood-brain barrier damage caused by early brain injury within 72 h after SAH, reduce the contents of Ibal and CD68 positive microglia. Intraventricular injection of Notchl receptor blockers and Notchl siRNA can inhibit the activation of Notchl pathway after SAH, mitigate brain tissue edema, blood-brain barrier damage, and neuronal apoptosis, as well as inhibit the activation of microglia and the release of inflammatory factors. Puerarin can inhibit the activation of Notchl receptor and downstream pathways, and simultaneously increase the content of Botch in brain tissue. Conclusion: Puerarin can inhibit the activation of Notchl receptor through Botch factor, thereby inhibiting the neuroinflammatory reaction mediated by Notchl pathway, and finally improve the early neurological dysfunction after SAH.